(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The relations between the Ottoman state and the khanates of Central Asia in Turkish historiography can be analyzed in two main periods. These relations are traced during the Ottoman Empire and the period of the Republic of Turkey. In the Ottoman era, studies on relations with Central Asia were extremely rare. However, during the Republic of Turkey, the Turkish Historical Society, founded at the initiative of Atatürk, paid special attention to the study of these relations along with other historical aspects. The article analyzes how Ottoman-Central Asian relations are reflected in Turkish historiography and which political, economic, and cultural issues are addressed.